METHODICAL APPROACHES TO THE FORMATION OF ADAPTIVE MANAGEMENT STRUCTURES - V. G. Antonov; I. A. Rumyantseva; T. Yu. Krotenko; O. G. Kazeeva (Вестник университета)
The article has been devoted to the formation of adaptive organizational management structures. The essence of structures and their relationship with other elements of the control system have been analyzed. Adaptability and flexibility are considered as the most important indicators of the efficiency of structures, their ability to ensure sustainable functioning and innovative development of enterprises. The mechanism of formation of adaptive structures has been presented. The issues about the quality of adaptation, the adaptive characteristics of the structure and their consistency with the level and quality of adaptation of other elements of the enterprise, the interface of adaptability and flexibility, the pace of change have been raised. It has been concluded, that the structure is not effective, if it does not seek adaptability. Meanwhile, the process of adaptation should be innovative and ensure effective innovation and technological development of the enterprise.